Cancer gene methylation detection system and cancer in-vitro detection method performed in system - LI YONGJUN; HAN XIAOLIANG; WU NINGNING; WANG JIANMING; GUO YUANYUAN (2021)
Disclosed herein is a system for detecting cancer methylation. The system comprises a sample collection module for collecting a subject sample, a DNA extraction module used for extracting and purifying DNA in the sample, a library building module used for building a DNA library for sequencing for the purified DNA sample, a conversion module used for converting the constructed DNA library by using a bisulfite, a pre-PCR amplification module used for carrying out pre-PCR amplification on the DNA library subjected to bisulfite conversion, a hybrid capture module used for carrying out hybrid capture on the sample subjected to the pre-PCR amplification by utilizing a probe composition, a post-PCR amplification module used for amplifying a product captured by hybridization by utilizing PCR, a sequencing module used for carrying out high-throughput next-generation sequencing on a product subjected to hybridization capture after PCR amplification, a data analysis module used for analyzing the sequencing data and dete